Research and Application of Optimization Transformation of Circulating Water Pump Impeller - Sheng, Li; Yanjie, Yin; Laragau, Muhammad Afuwan (Syntax Literate, 2024)
The reasons why the circulating water pump can only operate at less than 30 % of the outlet quick-closing valve opening are analyzed . The turning ratio law is used to calculate and analyze the turning size of the impeller. A plan for turning and modifying the circulating water pump impeller is proposed, which enables the circulating water pump outlet quick-closing valve to be fully opened and the motor current to operate within the allowable range. The economic efficiency of the circulating water pump impeller after modification is calculated, achieving the purpose of energy saving and consumption reduction. This study aims to analyze the causes of these inefficiencies and propose a solution by modifying the impeller through turning and recalibration. The turning ratio law was applied to calculate the appropriate size of the impeller, ensuring full valve opening while maintaining the motor current within permissible limits. Post-modification results demonstrated enhanced economic efficiency, reduced power consumption, and improved pump performance, achieving energy savings and consumption reduction. The study concludes that impeller turning is a practical and effective method for optimizing circulating water pump operations in thermal power plants.